Validation of a scale for the measurement of employee competency in relation to succession planning amongst administrators in higher education institutions - Muhamad Tasyrif, Ghazali (AOS-Estratagia and Inovacao, 2023)
Purpose: This paper examines the validity and reliability of an instrument to evaluate employee competency in the context of succession planning using a sample of administrators within the 48 to 54 grades in Malaysian public universities. Theoretical framework: Shaping the qualities and competencies of university administrators can serve as a model of competent leadership for the sustainability of succession planning for higher education institutions. Design/methodology/approach: Systematic random sampling was used for data collection using questionnaires, including pilot studies and subsequent field studies. The survey was administered to 430 respondents from the administrators of 20 public universities. The study conducted an exploratory factor analysis (EFA) using the pilot study data (n = 102) to identify potential factor structures. Confirmatory factor analysis (CFA) using field study data (n = 328) was conducted to confirm the construct measurement model. Findings: The EFA and CFA validation processes suggested that only 10 modified items with 4 components remained to achieve a better fit model: Interpersonal (IP), Personal Effectiveness (PE), Teamwork (TW), and Self-Development (SD). All composite reliability (CR) measures for these 4 components exceeded the required value of 0.6. Since the values of these indices fall within the range of their respective cutoff values, the model meets the goodness-of-fit criterion: RMSEA = 0.070,GFI=0.955, CFI = 0.953, TLI = 0.926, and a normalized chi-square = 2.605. According to the study, the instrument is valid and reliable for assessing the components of the employee competency model. Research, Practical & Social implications: The scale validated in this study could be used by human resource managers in public universities as a tool to better understand the belief systems of their employees. It could help them make an informed decision that will enable them to provide competent administrators for succession planning. Originality/value: This study is a catalyst to assess and highlight the current status and impact of employee competency on succession planning in Malaysian higher education institutions.